2015
DOI: 10.1371/journal.pone.0140630
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Nuclear Factor NF-κB Activation following Bone Trauma: A Pilot Study in a Wistar Rats Model

Abstract: The present study investigated the moment of peak NF-kB activation and its dissipation in the cortical bone in the femur of Wistar rat stimulated by surgical trauma. Sixty-five Wistar rats were divided into 13 groups (n = 5 per group): eight experimental groups (expG 1–8) divided based on the euthanasia time point (zero, 1 h, 2 h, 4 h, 6 h, 8 h, 12 h and 24 h) and five sham control groups (conG 1–5) killed at zero, 1 h, 2 h, 4 h and 6 h, respectively. A 1.8-mm-diameter defect was generated 0.5 mm from the femu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Other authors have reported that the drilling procedures for osteotomy should be minimally traumatic, which would be highly recommended to preserve the bone tissue by preventing damage to its healing potential [ 16 ]. In addition, the drilling to perform the surgical bed (osteotomy) for the installation of endosseous implants, produces a large local inflammatory reaction, which can be controlled and/or reduced by the use of adequate irrigation technique [ 5 ]. The results obtained in the present study showed a lower temperature rise in the groups where a single drill was used to perform the osteotomy (Con2 group and Test group), in comparison with the group where a drilling system with multiple drills (Con1 group) was used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors have reported that the drilling procedures for osteotomy should be minimally traumatic, which would be highly recommended to preserve the bone tissue by preventing damage to its healing potential [ 16 ]. In addition, the drilling to perform the surgical bed (osteotomy) for the installation of endosseous implants, produces a large local inflammatory reaction, which can be controlled and/or reduced by the use of adequate irrigation technique [ 5 ]. The results obtained in the present study showed a lower temperature rise in the groups where a single drill was used to perform the osteotomy (Con2 group and Test group), in comparison with the group where a drilling system with multiple drills (Con1 group) was used.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Salles and Collaborators (2015) [ 5 ], reported through an experimental study using an immunohistochemical analysis for the inflammatory factor NFkB (nuclear factor kappa-light-chain-enhancer of activated B cells), that irrigation plays an important role in controlling this endonuclease and, obviously, in controlling the intensity of the inflammatory process. In this sense, other histological studies have also shown that the healing response of bone tissue around implants can be improved when using drilling systems designed to reduce the trauma caused during osteotomy procedures [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, on the basis of the hypothesis that transcription factor NF-κB could be considered as a sensor of cellular and tissue stress, in the present study, NF-κB was selected as a stress marker and the presence of this protein as well as its peak of activation were evaluated through a specific technique developed by our group in different bone trauma situations [36,37]. Increased immunoreactivity for NF-κB observed in Wistar rat osteocytes after bone damage supports the idea of its significant role in bone remodeling and bone repair, regulating physiological processes involved in osteoclastic reabsorption and osteoblastic formation.…”
Section: Discussionmentioning
confidence: 99%
“…After perforation, muscle tissue and skin were closed through nylon 4.0 sutures. Euthanasia was performed after 6 h of the surgical procedure since this point in time corresponds to the peak time of NF-κB activation [36].…”
Section: Methodsmentioning
confidence: 99%
“…113 The traumatic signals caused by fracture and surgery initiate pro-inflammatory signaling cascades via activation of NF-κB transcription factors. 114,115 NF-κB activation leads to the production of high levels of NO and superoxide that mediate both bone damage and matrix degradation. 116 Mediators such as TNF-α, IL-1β, and matrix metalloproteinases (MMPs) play key roles in the pathogenesis of inflammatory bone diseases and injuries.…”
Section: Anti-inflammatory Effects Of Mechanical Loadingmentioning
confidence: 99%